2003
DOI: 10.1038/sj.ejcn.1601906
|View full text |Cite
|
Sign up to set email alerts
|

Mild dehydration: a risk factor of broncho-pulmonary disorders?

Abstract: Several expert committees recommend a high fluid intake in patients with chronic bronchitis and asthma. Is there a relationship between fluid intake or hydration status and broncho-pulmonary disorders like bronchitis and asthma? First, basic physiologic mechanisms like regulation of lung fluid balance and water transport at pulmonary surfaces were analyzed, in order to characterize the role of local hydration status in lung and airways. Second, making use of the computerbased literature searches (PubMed), evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 49 publications
1
21
0
1
Order By: Relevance
“…Improvement of systemic hydration status has not been demonstrated to be clinically effective in disorders of the lungs and airways [76]. However, local water transport and hydration status of mucus play a critical role in the pathogenesis of Hydration and Disease 538S VOL.…”
Section: Local Mild Hypohydration or Dehydration Bronchopulmonary Dismentioning
confidence: 99%
“…Improvement of systemic hydration status has not been demonstrated to be clinically effective in disorders of the lungs and airways [76]. However, local water transport and hydration status of mucus play a critical role in the pathogenesis of Hydration and Disease 538S VOL.…”
Section: Local Mild Hypohydration or Dehydration Bronchopulmonary Dismentioning
confidence: 99%
“…It is interesting to note that antihypertensive medication is currently prescribed against these very same hormones (Deedwania, 2007;Nesbitt, 2007). In 2002, a meeting was organized in Dortmund to study the physiological effects of mild dehydration, yet the majority of presentations showed the benefits of increased consumption of fluid, be it at the level of cognition (Wilson and Morley, 2003), exercise performance (Maughan, 2003), urolithiasis Beverage intake in the French F Bellisle et al (Siener and Hesse, 2003), urinary tract infection (Beetz, 2003), dental disease (Smith and Shaw, 2003), constipation (Arnaud, 2003) or even broncho-pulmonary infection (Kalhoff, 2003). Such reports are the outcome of scientific studies, rather than 'urban myths found on the Internet' (Negoianu and Goldfarb, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition and Diarrhoea increase the risk of pneumonia among young age group (Sania Ashraf et al, 2013;Coles CL et al, 2005). Dehydration caused by diarrhoea may also increase the risk of respiratory illnesses (Kalhoff H., 2003). Reducing child mortality is one of the eight Millennium Development Goals (MDGs), which are the world's time-bound targets for reducing poverty in its various dimensions by 2015.…”
Section: Introductionmentioning
confidence: 99%